Can We "Predict" Long‐Term Outcome for Ambulatory Transcutaneous Electrical Nerve Stimulation in Patients with Chronic Pain?. Issue 3 (17th January 2014) - Köke, Albère J.; Smeets, Rob J.E.M.; Perez, Roberto S.; Kessels, Alphons; Winkens, Bjorn; van Kleef, Maarten; Patijn, Jacob
Abstract Background Evidence for effectiveness of transcutaneous electrical nerve stimulation (TENS) is still inconclusive. As heterogeneity of chronic pain patients might be an important factor for this lack of efficacy, identifying factors for a successful long‐term outcome is of great importance. Methods A prospective study was performed to identify variables with potential predictive value for 2 outcome measures on long term (6 months); (1) continuation of TENS, and (2) a minimally clinical important pain reduction of ≥ 33%. At baseline, a set of risk factors including pain‐related variables, psychological factors, and disability was measured. Results In a multiple logistic regression analysis, higher patient's expectations, neuropathic pain, no severe pain (< 80 mm visual analogue scale [VAS]) were independently related to long‐term continuation of TENS. For the outcome "minimally clinical important pain reduction, " the multiple logistic regression analysis indicated that no multisited pain (> 2 pain locations) and intermittent pain were positively and independently associated with a minimally clinical important pain reduction of ≥ 33%. Conclusion The results showed that factors associated with a successful outcome in the long term are dependent on definition of successful outcome.